Emerging RHDV2 suppresses the impact of endemic and novel strains of RHDV on wild rabbit populations. Issue 3 (13th January 2020) - Ramsey, David S. L.; Cox, Tarnya; Strive, Tanja; Forsyth, David M.; Stuart, Ivor; Hall, Robyn; Elsworth, Peter; Campbell, Susan
Abstract: Multi‐strain, host‐disease dynamics describe a system where multiple strains of a pathogen compete for susceptible individuals of a single host. The theoretical properties of these systems have been well studied, but there are few empirical studies in wildlife hosts. We examined the impacts of two novel strains of rabbit haemorrhagic disease virus (RHDV) recently introduced into Australia, one inadvertently (RHDV2) and one deliberately for rabbit biocontrol (RHDV‐K5), by analysing long‐term monitoring data for introduced European rabbits Oryctolagus cuniculus from 18 sites throughout Australia. We examined population‐level impacts using rabbit spotlight counts pre‐ and post‐arrival of the two strains. We also analysed serological data to determine potential interactions among the introduced and existing field strains of RHDV, as well as a pre‐existing benign strain of calicivirus (RCV‐A1). Serological analyses suggested that RHDV2 arrived in Australia during spring 2014 and spread rapidly through the Australian rabbit population within 2 years. Following the establishment of RHDV2, rabbit abundance was reduced by an average of 60%, with impacts most pronounced in South and Western Australia. In contrast, the deliberate release of RHDV‐K5 had little impact on rabbit populations. Although RHDV2 has spread rapidly throughout Australia, our serological analyses do not support the observation that RHDV2 is rapidly replacing existing field strains of RHDV, as was previously reported in Australia and Europe. Nevertheless, RHDV2 has negatively impacted the ability of RHDV and RCV‐A1 to spread within rabbit populations, most likely due to its ability to infect juvenile rabbits, thereby removing them from the pool of susceptible individuals available to be infected by competing strains. Synthesis and applications. The impact of the release of a novel strain of rabbit haemorrhagic disease virus (RHDV‐K5) for rabbit biocontrol in Australia has been suppressed by the emergence of a competing strain, RHDV2. Hence, the success of further releases of similar RHDV strains for rabbit biocontrol appears doubtful. Despite this, RHDV2 has suppressed rabbit abundances by an average of 60%, with impacts most pronounced in South and Western Australia. Whether the incursion of RHDV2 leads to the competitive exclusion of other endemic RHDV strains remains to be resolved. However, the existence of partial cross‐immunity could allow some level of coexistence between RHDV2 and RHDV strains, at least in the medium term. Abstract : The impact of the release of a novel strain of rabbit haemorrhagic disease virus (RHDV‐K5) for rabbit biocontrol in Australia has been suppressed by the emergence of a competing strain, RHDV2. Hence, the success of further releases of similar RHDV strains for rabbit biocontrol appears doubtful. Despite this, RHDV2 has suppressed rabbit abundances by an average of 60%, with impacts most pronounced in South and Western Australia. Whether the incursion of RHDV2 leads to the competitive exclusion of other endemic RHDV strains remains to be resolved. However, the existence of partial cross‐immunity could allow some level of coexistence between RHDV2 and RHDV strains, at least in the medium term.